The Synergy of Sustainable Financial Strategies and Sustainability Performance: A Case Study of PT Mitra Tani 27 (Top Leader of Agro-Industrial Companies in East Java) - Novi Wulandari WIDIYANTI; Agung Budi SULISTIYO; Muhammad MIQDAD; Bayu APRILLIANTO (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to explore the sustainability strategies and how they impact the sustainability performance of PT Mitra Tani 27. This research is a type of qualitative research with a case study approach—the data collection for this research using in-depth interviews, documentation, and observations. In-depth interviews were established at different times by having personal interviews with the informant. The validity test of the data used the credibility testing approach and the transferability test. The study results show that the sustainable finance strategy includes six main principles: Trust, Competent, Harmonious, Loyal, Adaptive, and Collaborative. The company's economic performance illustrated increased sales intensity and volume, especially edamame production. The sales of edamame products have expanded to various countries, with a volume of 7,578 tons for the export market and 1,817 tons for the domestic market every year. The company's commitment to applying the 4R-based principles (Reduce, Reuse, Recycle, and Replace) describes the primary environmental performance. The company's social performance reflects its commitment to providing consumers with high-quality products and services.